Correct two-phase and one-phase deadlock detection algorithms for distributed systems - Kshemkalyani, A.D.; Singhal, M. (Parallel and Distributed Processing, 2nd IEEE Symposium On, 1990)
The authors propose a correction to the two-phase deadlock detection algorithm, which has been shown to be incorrect. They prove the correctness of the modified algorithm using a stable property detection technique that observes the system at an absolute time instant. They then use the notion of consistent cuts and vector time to give a simple one-phase deadlock detection algorithm.< >